The ERATOSTHENES Remote Sensing Supersite: Ground-truth observations over Cyprus - Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Ansmann, Albert; Bühl, Johannes; Seifert, Patric; Baars, Holger; Amiridis, Vassilis; Wandinger, Ulla; Hadjimitsis, Diofantos G. (My University, 2020)
Cyprus is strategically located in the region of the Eastern Mediterranean, the Middle East and North Africa (EMMENA). As a crossroad between Europe, Asia and Africa, it is representative of meteorological conditions and coastal areas in the EMMENA region. Incomplete coverage with ground monitoring stations is the main limitation to make fast and significant progress in understanding the complex climate-relevant atmospheric processes around the globe and thus to improve atmospheric models used for climate change projections and extreme weather predictions. Although satellites can continuously monitor the atmosphere on a regional to global scale, they must be ground-calibrated and validated in order to incorporate satellite data into atmospheric models.